The heart of higher education : a call to renewal : transforming the academy through collegial conversations - Palmer, Parker J.; Zajonc, Arthur; Scribner, Megan (San Francisco : Jossey-Bass, 2010)
"A call to advance integrative teaching and learning in higher education. From Parker Palmer, best-selling author of The Courage to Teach, and Arthur Zajonc, professor of physics at Amherst College and director of the academic program of the Center for Contemplative Mind in Society, comes this call to revisit the roots and reclaim the vision of higher education. The Heart of Higher Education proposes an approach to teaching and learning that honors the whole human being--mind, heart, and spirit--an essential integration if we hope to address the complex issues of our time. The book offers a rich interplay of analysis, theory, and proposals for action from two educators and writers who have contributed to developing the field of integrative education over the past few decades. Presents Parker Palmer's powerful response to critics of holistic learning and Arthur Zajonc's elucidation of the relationship between science, the humanities, and the contemplative traditions. Explores ways to take steps toward making colleges and universities places that awaken the deepest potential in students, faculty, and staff. Offers a practical approach to fostering renewal in higher education through collegiality and conversation. The Heart of Higher Education is for all who are new to the field of holistic education, all who want to deepen their understanding of its challenges, and all who want to practice and promote this vital approach to teaching and learning on their campuses."--
Machine generated contents note: Foreword (Mark Nepo). -- Gratitudes. -- The Authors. -- Introduction. -- 1 Toward a Philosophy of Integrative Education. -- 2 When Philosophy Is Put into Practice. -- 3 Beyond the Divided Academic Life. -- 4 Attending to Interconnection, Living the Questions. -- 5 Experience, Contemplation and Transformation. -- 6 Transformative Conversations on Campus. -- Afterword. -- About the Appendices: Experiments in Integrative Education. -- Appendix A In the Classroom. -- Appendix B Beyond the Classroom. -- Appendix C Administrative and Campuswide Initiatives. -- Endnotes.
Includes bibliographical references and index.
Keywords: Education, Higher -- Philosophy; Educational change; Educational innovations